Employee Performance: The Role Of Work Experience, Motivation, And Work Engagement - Asri Endang Kuswandari; Desi Tri Kurniawati; Ana Sofia Aryati (Yayasan Darussalam Bengkulu, 2026)
Background This study investigates the role of work engagement as a mediating mechanism in the relationship between work experience, work motivation, and employee performance within the context of energy transition at PT Paiton Operation and Maintenance Indonesia. Grounded in the Job Demands–Resources (JD-R) framework, the study emphasizes that individual resources such as experience and motivation can enhance employee performance through the development of positive psychological engagement. Method This research employed an explanatory quantitative approach. Data were collected from 423 employees of PT Paiton Operation and Maintenance Indonesia using structured questionnaires. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the direct and mediating relationships among work experience, work motivation, work engagement, and employee performance. Results The findings reveal that work experience and work motivation have significant positive effects on both work engagement and employee performance. In addition, work engagement significantly enhances employee performance and partially mediates the relationships between work experience, work motivation, and performance. These results demonstrate that employees with greater experience and stronger motivation are more likely to develop higher engagement, which subsequently improves performance outcomes. Conclusion This study extends the Job Demands–Resources (JD-R) framework by confirming that employee performance is influenced not only by individual resources but also by the extent to which these resources are transformed into positive psychological states through work engagement. The findings underscore the strategic importance of fostering employee engagement to sustain performance in high-risk and energy transition organizational environments.